Tides of the Ross Sea and Ross Ice Shelf cavity - PADMAN, LAURENCE; EROFEEVA, SVETLANA; JOUGHIN, IAN (Antarctic Science, 2003)
Two new ocean tide models for the Ross Sea including the ocean cavity under the Ross Ice Shelf, are described. The optimum model for predicting ice shelf surface height variability is based on assimilation of gravimetry-derived tidal constituents from the Ross Ice Shelf. Synthetic aperture radar interferograms provide an independent test of model performance. The standard deviation of tide height variability is largest under the eastern ice shelf along the Shirase and Siple Coasts, where it can exceed 0.8 m. The maximum peak-to-peak tidal range in this region is ∼3 m. The best predictor for ocean tidal currents north of the ice front is a dynamics-based model that solves the depth-integrated shallow water equations with a linear representation of benthic friction rather than the more usual quadratic form. Tidal currents over the open Ross Sea are dominated by diurnal, topographically trapped vorticity waves. The strongest modelled currents exceed 1 m s −1 at spring tide in a narrow band along the upper continental slope in the north-western Ross Sea. Typical tidal currents in the central continental shelf area of the Ross Sea are 10–20 cm s −1 . Under the ice shelf the typical currents are ∼5 cm s −1 .